2007
DOI: 10.1021/jp0710739
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics and Photochemistry of Imipramine, Desimipramine, and Clomipramine in Several Solvents:  A Fluorescence, 266 nm Laser Flash, and Theoretical Study

Abstract: Imipramine (IPA) and its derivatives are used widely for the treatment of depression and other mental disorders. Although there are more than 20 FDA-approved antidepressant drugs, the search continues for better compounds with fewer deleterious side effects and higher efficacy. Over the past decade, several classes of antipsychotic drugs have been developed, which-in spite of their structural diversity-share an ability to modulate neurotransmission and to produce undesirable side effects. Phototoxicity is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Fluorescence quantum yields of 0.0034 and 0.0022 were obtained for zCPTX and zCPTX–HCl, respectively. These low ϕ f values correspond very well with those reported for the promazines (10) and imipramines (6). As in the case of these structurally related drugs, fluorescence is not the major S 1 deactivation process for CPTX.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Fluorescence quantum yields of 0.0034 and 0.0022 were obtained for zCPTX and zCPTX–HCl, respectively. These low ϕ f values correspond very well with those reported for the promazines (10) and imipramines (6). As in the case of these structurally related drugs, fluorescence is not the major S 1 deactivation process for CPTX.…”
Section: Resultssupporting
confidence: 89%
“…Then 10 μL of this mixture was injected at least three times into the HPLC to determine the quantity of remaining starting material. The quantum yield was then calculated as explained elsewhere (6). Briefly, the slope of the linear part of the concentration–time curve is equal to the rate of the zeroth‐order reaction ( k ), V is the irradiated volume (3 mL), I 0 is the lamp intensity at 313 nm, [zCPTX] 0 is the initial drug concentration, and α is the fraction of zCPTX that has reacted.…”
mentioning
confidence: 99%
“…In general, these results indicate that the reactivity of the TCA derivatives is similar in the reaction with the manganese(III) ion. The higher reactivity of the phenothiazine derivatives would be expected for simple electron transfer processes, because the presence of the sulfur atom decreases the reduction potential [37]. This phenomenon is not observed in the reaction with the manganese(III) ion, [24].…”
Section: Resultsmentioning
confidence: 86%
“…The authors considered that the PTL-HCl triplet state may be associated with the in vivo phototoxic effects of this drug [18]. In line with these experiments, the tricyclic antidepressants (TCAs) - Imipramine (IPA), desimipramine (DIPA) and clomipramine (CIPA) - photophysical properties were studied in different solvents [19]. It was shown that the primary transient intermediates produced by 266 nm high-intensity laser photolysis are the solvated electron and the corresponding radical cation, consistent with the results reported in [18].…”
Section: Introductionmentioning
confidence: 99%